2020
DOI: 10.3389/fphar.2020.00478
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Combined With Chemotherapy and Cetuximab or Bevacizumab for Metastatic Colorectal Cancer: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Background: Huangci Granule is a traditional Chinese medicine for treating metastatic colorectal cancer (mCRC). Objective: To evaluate the efficacy and safety of Huangci Granule combination with chemotherapy and cetuximab (CET) or bevacizumab (BV) for treating mCRC. Methods: We performed a randomized, controlled, and double-blind trial and recruited patients with mCRC who were planned to undergo chemotherapy combined with CET or BV. The treatment group was treated with Huangci Granule, while the control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…Indeed, many chemotherapeutics derived from plants, such as paclitaxel, vinblastine, and vincristine, have proven effective against different tumors. Sometimes as a complementary therapy, medicinal plants are widely used to treat several types of cancers, including CRC, with relatively fewer and milder side effects [9,10]. As an important source of alternative and complementary medicines, traditional Chinese medicine (TCM) has been widely reported to treat cancer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many chemotherapeutics derived from plants, such as paclitaxel, vinblastine, and vincristine, have proven effective against different tumors. Sometimes as a complementary therapy, medicinal plants are widely used to treat several types of cancers, including CRC, with relatively fewer and milder side effects [9,10]. As an important source of alternative and complementary medicines, traditional Chinese medicine (TCM) has been widely reported to treat cancer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As an important source of alternative and complementary medicines, traditional Chinese medicine (TCM) has been widely reported to treat cancer [11][12][13]. In recent years, more and more herbs originating from TCM have attracted considerable attention as anti-CRC agents because of their therapeutic value and low toxicity [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Both in vitro and in vivo experiments showed that this formula can inhibit the invasion and metastasis of colon cancer (9,10). A randomized, controlled, and double-blinded clinical trial confirmed that PRM1201 combined with chemotherapy and Cetuximab or Bevacizumab can prolong the progression free survival of metastatic colorectal cancer (11). To determine whether PRM1201 can benefit patients with colon cancer in an earlier stage, we conducted this prospective interventional study in patients with stage III colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicines (TCM) have several advantages in the treatment of malignancies with low toxicity. 18 Therefore, TCM have received wide attention recently. 19 CCM is a well-known dietary polyphenol derived from the rhizomes of turmeric.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop more effective and safe drugs. Traditional Chinese medicines (TCM) have several advantages in the treatment of malignancies with low toxicity 18 . Therefore, TCM have received wide attention recently 19 .…”
Section: Introductionmentioning
confidence: 99%